Witnessing the Waste Land: A Phenomenological Account of Landscape and its Discontents - Allwood, Mark (Imaginations)

(untitled) (York University, 2024)
“Witnessing the Waste Land: A Phenomenological Account of Landscape and its Discontents” is a text and image experiment centred around the urban wilderness of Tommy Thompson Park in Toronto, Ontario. The text can be read in numerous ways by oscillating between philosophical thought, poetry, photography, stream of consciousness, and the analysis and inclusion of documents. In some ways this approach is an imitation and a reaction to the postmodern urban schizophrenia one encounters at a park that operates as a waste disposal facility, a habitat for flora and fauna, a research centre, a bike trail, a habitat creation project, a birder’s paradise, and a waste land.